Better communication with migrant communities during COVID-19 pandemic:a portuguese experience. (20th October 2021) - Neto, J; Carvalho, C; Letras, S
Abstract: : Odemira, in the southeast litoral of Portugal, has 33% of migrant citizens, mostly from Southeast Asia, going up to 50% counting transient citizens. Most of them do not speak English, making communication with health services difficult. They tend to live in overcrowded houses with unsanitary conditions. With the emergence of the COVID-19 pandemic, all the above resulted in high incidence and ineffective contact tracing (CT), testing and isolation by the public health teams. It was essential to develop strategies to manage and control outbreaks, and also to achieve health equity. Our experience can be useful for other countries in dealing with their multicultural communities. This intervention started in march 2020 and is still ongoing. The aims were to improve the accuracy of epidemiological surveys (ES) and CT, to more easily stop transmission, to develop the communication skills of health professionals and to improve migrant's healthcare access. For this, the focus was on digital written communication tools (Whatsapp, translation apps). It was created a toolkit to guide ES and CT tailored to the migrant population, with tips and best practices, and used translated information materials about preventive COVID-19 measures. Workshops were led with health professionals. It was stablished work with local NGOs, creating social media campaigns during crucial events (Holi holliday). As results. it was achieved a better ES output, more accurate CT and better transmission control, with noticeable differences between march 2020 and now. The relationship with this community improved, having better access to services and their needs met. Health professionals reported being more at ease dealing with these patients. Our experience shows it's possible to communicate effectively despite language and cultural barriers, that cultural knowledge is important in advancing public health goals and that multidisciplinary and intersectoral work is essential to effective interventions. Key messages: This intervention allowed us to achieve a better output of epidemiological surveys, more accurate contact tracing and were more effective in breaking transmission chains and controlling outbreaks. It was achieved a better understanding and relationship with this community, with better ability to respond to their needs and promoting their access to healthcare.